Chemical Strain Engineering of Magnetism in Oxide Thin Films. Issue 22 (3rd April 2017) - Copie, Olivier; Varignon, Julien; Rotella, Hélène; Steciuk, Gwladys; Boullay, Philippe; Pautrat, Alain; David, Adrian; Mercey, Bernard; Ghosez, Philippe; Prellier, Wilfrid
Abstract : Transition metal oxides having a perovskite structure form a wide and technologically important class of compounds. In these systems, ferroelectric, ferromagnetic, ferroelastic, or even orbital and charge orderings can develop and eventually coexist. These orderings can be tuned by external electric, magnetic, or stress field, and the cross‐couplings between them enable important multifunctional properties, such as piezoelectricity, magneto‐electricity, or magneto‐elasticity. Recently, it has been proposed that additional to typical fields, the chemical potential that controls the concentration of ion vacancies in these systems may reveal an efficient alternative parameter to further tune their properties and achieve new functionalities. In this study, concretizing this proposal, the authors show that the control of the content of oxygen vacancies in perovskite thin films can indeed be used to tune their magnetic properties. Growing PrVO3 thin films epitaxially on an SrTiO3 substrate, the authors reveal a concrete pathway to achieve this effect. The authors demonstrate that monitoring the concentration of oxygen vacancies through the oxygen partial pressure or the growth temperature can produce a substantial macroscopic tensile strain of a few percent. In turn, this strain affects the exchange interactions, producing a nontrivial evolution of Néel temperature in a range of 30 K. Abstract : The control of the content of oxygen vacancies in PrVO3 perovskite thin films, epitaxially grown on SrTiO3, is used to tailor their magnetic properties. Through the oxygen partial pressure or the growth temperature control, a substantial macroscopic tensile strain of a few percent is produced. In turn, this strain affects the exchange interactions, producing a nontrivial evolution of the Néel temperature.